The implementation of Shariah governance framework of 2010: advantages and constraints - Omar, Muhammad Naim; Hassan, Rusni; Arifin, Mahamad; Mohd Napiah, Mohammad Deen; Othman, Ahmad Azam; Abdullah, Mohamad Asmadi; Yusoff, Adnan (AENSI Journals, 2014)
The Central Bank of Malaysia (hereinafter referred to BNM) has introduced the guideline on Shariah Governance Framework for Islamic Financial Institutions (IFIs)(hereinafter referred to as SGF 2010) in October 2010 to have proper Shariahgovernance. All Islamic Financial Institutions in Malaysia are required to adopt SGF 2010 effectively on 1st January 2011, giving the IFIs six months to comply with. Within such period, the IFIs need to confirm that they have met all the requirements and are operating in accordance with it. After one year of the implementation there is a need to study the effects of SGF 2010 on IFIs.Thus, this article investigates the advantages and constraints resulting from the implementation of SGF 2010.. The findings and analysis show that the SGF was well received by IFIs. However there are few constraints and challenges need to be rectified.. This survey was conducted through the collection of data and information by distributing the questionnaire to the respondents who are involved in IFIs’ industries such as the management of the IFIs, be it Islamic banks and Takaful institutions, Shariah Committee and Shariah Officers. Most of the data in this study were collected and analyzed using the Statistical Package for Social Sciences (SPSS) software version 16.0 and Microsoft Excel. Additional the descriptive analysis is used to determine the number of frequencies and percentages